An illustrated prehistory of the Jubbah oasis: Reconstructing Holocene occupation patterns in north‐western Saudi Arabia from rock art and inscriptions. (24th November 2017) - Guagnin, Maria; Shipton, Ceri; al‐Rashid, Moudhy; Moussa, Fares; El‐Dossary, Sarah; Sleimah, Mona Bin; Alsharekh, Abdullah; Petraglia, Michael
Abstract: A systematic survey of rock art and associated archaeological features in the Jubbah oasis provides evidence of Holocene occupation from the early Holocene to the present. In total 1249 panels with rock art and inscriptions, and 159 archaeological sites, were recorded on twelve different jebels. Analyses of rock art content and engraving stratigraphy indicate that the iconic Jubbah style had a long tradition among pre‐pastoral hunters and continued to be used by early herders. We also identify a distinct body of rock art that pre‐dates the Jubbah style and may be associated with a nearby Epipalaeolithic site. Our systematic dataset identifies a body of Bronze Age rock art that is further supported by the material culture and radiocarbon dates obtained from the remains of disturbed cairns. The rock art in Jubbah appears to have been created throughout the Holocene occupation of the oasis and similarities in the representation of animals, choice of location and content of rock art scenes are evident from the Bronze Age to the early modern period, and perhaps into the twentieth century. Moreover, rock art and epigraphy suggest that occupation phases in Jubbah were sustained long enough for the repeated development of unique local characteristics throughout the Holocene.